HUBUNGAN KOLESTEROL NONHDL TERHADAP FUNGSI KOGNITIF PADA PASIEN STROKE ISKEMIK DENGAN DEFISIT NEUROLOGIS RINGAN - Aylenia Lysandra,* Budi Riyanto Wreksoatmodjo,** Josephine Retno Widayanti** (Neurona Majalah Kedokteran Neuro Sains, 2020)
INTRODUCTION ISCHEMIC STROKE PATIENTS HAVE HIGHER RISK OF COGNITIVE DECLINE SEVERITY OF COGNITIVE IMPAIRMENT DEPENDS ON THE SEVERITY OF NEUROLOGICAL DEFICIT THE SEVERITY OF COGNITIVE IMPAIRMENT IS ALSO AFFECTED BY ABNORMAL NONHDL CHOLESTEROL LEVEL WHICH INCLUDES ATHEROGENIC LIPID THAT CAUSES ATHEROSCLEROSIS